Fitting Gas Permeable Contact Lens in Keratoconus; Still a Challenge? - Sara Ortiz-Toquero; Raúl Martín (The Ophthalmology, 2016)
Gas permeable (GP) contact lenses (CL) are of paramount importance in keratoconus patient management1 to rehabilitate vision and improve patients’ quality of life (QoL).2 Different surgical and non-surgical options are available in keratoconus management. Early stages could be managed with conventional optical corrections (spectacles and/or soft CL), however if disease progress, and corneal irregularity affects to visual acuity GP (conventional or with keratoconus specific design) lenses should be necessaries to patients’ visual rehabilitation. Other alternative CL options (piggy-back, mini-scleral, semi-scleral, scleral designs etc.) have been, also, proposed. If patients show CL intolerance or disease progresses and/or corneal integrity could be affected surgical techniques are required.